Practice patterns and predictors of outpatient care following acute kidney injury in an Australian healthcare setting. Issue 1 (20th January 2022) - See, Emily J.; Ransley, David G.; Polkinghorne, Kevan R.; Toussaint, Nigel D.; Bailey, Michael; Johnson, David W.; Robbins, Ray; Bellomo, Rinaldo
Abstract: Background: Survivors of acute kidney injury (AKI) are at increased risk of major adverse kidney events and international guidelines recommend individuals be evaluated 3 months following AKI. Aim: We describe practice patterns and predictors of post‐AKI care in an Australian tertiary hospital. Methods: A retrospective analysis was undertaken of adults with AKI (defined by KDIGO criteria) admitted to a single centre between 2012 and 2016. The primary outcome was outpatient nephrology review at 3 months. Secondary outcomes included inpatient nephrology review, and outpatient serum creatinine and urinary protein measurements. Data were analysed using multivariable logistic and competing risk regression. Results: Only 117 of 2111 (6%) patients with AKI were reviewed by a nephrologist at 3 months. Reviewed patients were more likely to have a higher discharge serum creatinine (odds ratio (OR) 1.20 per 10 μmol/L increase; 95% confidence interval (CI) 1.16–1.25) or a history of peripheral vascular disease (OR 1.77; 95% CI 1.00–3.14). They were less likely to be older (OR 0.66 per decade; 95% CI 0.57–0.76) or to have a history of liver (OR 0.47; 95% CI 0.26–0.87) or ischaemic heart (OR 0.50; 95% CI 0.27–0.94) disease. AKI stage did not predict follow up. The median time from discharge to outpatient serum creatinine testing was 12 days (interquartile range 4–47) and proteinuria was measured in 538 (25%) patients. Conclusions: A minority of admitted AKI patients receive recommended post‐AKI care. Studies in other Australian institutions are required to confirm or refute these concerning findings.